Enhancing English Speaking Skills Through Blended Learning: A Study on Medical Record Program - Lidia Deviga (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The globalized landscape of healthcare services demands that Medical Record professionals possess proficient English communication skills, particularly in international coding standardizations (ICD-10/ICD-11), patient admissions, and inter-professional reporting. However, non-linguistic healthcare students often face high speaking anxiety and limited classroom exposure. This study evaluates the effectiveness of a Blended Learning model in enhancing the English speaking skills of second-semester Medical Record students at Universitas Bhakti Hasta Mulia Madiun. A quantitative pre-experimental design (one-group pre-test/post-test) was deployed, involving 52 students (40 females and 12 males). The blended framework integrated synchronous face-to-face communicative simulations (medical role-playing) with asynchronous digital platforms (Learning Management System and video-recording tasks). Speaking proficiency was measured using an analytical rubric assessing pronunciation, fluency, grammar, vocabulary, and professional comprehension. Data analysis via paired sample t-test revealed a highly significant improvement from pre-test (M = 62.45) to post-test (M = 78.12), with p < 0.001. Female students demonstrated higher baseline scores, whereas male students exhibited a higher rate of progression. The study concludes that blended learning optimizes pedagogical flexibility, mitigates speech anxiety, and significantly upgrades professional English speaking outcomes in vocational medical contexts.